Synthesis, characterization and biocompatibility studies on chitosan-graft-poly(EGDMA) - Adali, Terin; Yilmaz, Elvan (Elsevier Sci Ltd, 2009)
Poly(ethylene glycol dimethacrylate), poly(EGDMA), was grafted onto chitosan by using a redox initiation system. Chitosan-graft-poly(EGDMA) products were characterized by DSC, TGA, FTIR and XRD techniques. Chitosan-graft-poly(EGDMA) was found to be enzymatically degradable in aqueous solutions of lysozyme, lipase and a mixture of a-amylase and protease. The biocompatibility of chitosan-graft-poly (EGDMA) with 871% grafting yield was investigated by studying its cytotoxicity, sensitization, irritation, acute systemic toxicity and hemolytic activity. The results of biocompatibility experiments showed that the product can potentially be used for external intervention devices on bone and other tissue. (C) 2009 Published by Elsevier Ltd.
Keywords: Biocompatibility; Biodegradability; Cerium(IV); Copolymerization; Dimethacrylate